Respons in growth and production of soybean (Glycine max (L.) Merrill) to application of municipal waste compost and P fertilizer - Rasi Kasim Samosir; Ratna Rosanty Lahay (Universitas Sumatera Utara, 2016)
This research was conducted to obtain dose of municipal waste compost and P fertilizer which can improve the growth and production of the soybean. The research was conducted at experimental field of Agricultural Faculty of Sumatera Utara University, Medan which about ± 25 metres above sea level, begun from April to July 2015 using factorial randomized block design with two factors, i.e: doses of municipal waste compost (0 g/plant, 15 g/plant, 30 g/plant, and 45 g/plant) and doses of P fertilizer (0 g/plant, 1.5, and 3 g/plant). Parameters observed were plant height, stem diameter, number of books per plant, number of pods per plant, number of pods per plant lists, number of seeds per plant, seeds per plant weight, weight 100 seeds, and production of seeds per plots. The results showed that application of municipal waste compost significantly affected stem diameter at 2, 4, 5 weeks after planting,production of seeds per plots. Application of P fertilizer significantly affected number of pods per plant lists, number of seeds per plant, and seeds per plant weight. Interaction between aplication of municipal waste compost and P fertilizer not significantly affected on all parameters of observation.